The University Conception of Ivane Javakishvili - Sartania, Davit (Politics / პოლიტიკა, 2022)
Ivane Javakhishvili, who lived in the second half of the 19 th century and the first half of the 20 th century, is one of the leading figures of the foundation and development of the new Georgia. The events that developed at the beginning of the 20 th century (the First World War and the revolution in the Russian Empire) determined the future fate of Georgia. Ivane Javakhishvili met the changes caused by these events prepared and took appropriate action. In particular, it was the recognition of the role of science, which entered the life of each advanced country on an unprecedented scale and showed its vitality. With Ivane Javakhishvili's initiative, science should be revived in Georgia, for which a university should be established in Georgia. According to Ivane Javakhishvili's concept, the Georgian university should be adapted to the needs of the Georgian nation, and therefore it should be different from other universities in terms of structure and content of study programs. This difference gave us a new, Georgian model of the university.